Aplicación de ácido salicílico y miel en el crecimiento y rendimiento de tomate Solanum lycopersicum en malla sombra - Soriano Sánchez, Ulises (Universidad Michoacana de San Nicolas de Hidalgo, 2024)
Salicylic acid is a plant growth regulator that can promote increased production of horticultural crops. In addition, the effect of the application of honey on the growth, development and vigor of the plants has been found. The objective was to evaluate the foliar application of salicylic acid and honey on the growth and yield of tomato grown under shade mesh conditions. The crop was established in Apatzingán, Michoacán under shade mesh conditions. The tomato variety was PRIMUS LF with determined growth. The treatments consisted of the application of salicylic acid (SA) and honey, alone and in combination, in two (A2), four (A4) and six (A6) applications. The applications of the treatments began 10 days after the transplant at application intervals of 10 days, until reaching day 60. The experimental design was a complete randomized block design with four replications. The results indicate that with the application of AS-A2, the plants registered the highest heights (94 cm) and more leaves per plant (41.62). In the case of stem diameter, it was with AS-M-A4 that the highest value was forced (10.67 mm). The most productive plants in fruit yield were those treated with M-A4 (3639.3 g) and with M-A2 (2762.3 g). Honey at 4 applications increased a 26.4% more number of fruits, while in the diameter variable polar and equatorial, no statistically significant differences were obtained, the AS-A4 the highest weight of dry leaf was presented. The application of honey proved to be a good option to increase the yield and the number of fruits in the crop.

El ácido salicílico es un regulador de crecimiento de las plantas que puede favorecer el incremento de la producción de los cultivos hortícolas. Así mismo, se ha encontrado efecto positivo de la aplicación de miel de abeja sobre el crecimiento, desarrollo y vigor de las plantas. El objetivo fue evaluar la aplicación foliar del ácido salicílico y miel en la producción de tomate bajo condiciones de malla sombra. El cultivo se estableció en Apatzingán, Michoacán bajo condiciones de malla sombra. La variedad de tomate fue PRIMUS LF de crecimiento determinado. Los tratamientos consistieron en la aplicación de ácido salicílico (AS) y miel, solos y combinados, en dos (A2), cuatro (A4) y seis (A6) aplicaciones. El diseño experimental fue de bloques completos al azar con cuatro repeticiones. Los resultados indican que con la aplicación de AS-A2 las plantas registraron las mayores alturas (94 cm) y más hojas por planta (41.62). En el caso del diámetro de tallo, fue con AS-M-A4 que se logró el valor más elevado (10.67 mm). Las plantas más productivas en rendimiento de frutos fueron las tratadas con M-A4 (3639.3 g) y con M-A2 (2762.3 g). La Miel a 4 aplicaciones incremento en 26.4 % el número de frutos, mientras que en la variable de diámetro polar y ecuatorial no se obtuvieron diferencias estadísticamente significativas, con el tratamiento AS-A4 se presentó el mayor peso de hoja seca. La aplicación de miel mostró ser una buena opción para incrementar el rendimiento y el número de frutos en el cultivo.
Facultad de Ciencias Agropecuarias. Maestría Interinstitucional en Agricultura Protegida
Keywords: info:eu-repo/classification/cti/6; FCA-M-2024-0003; Materia seca; Producción de fruto; Suministro foliar; http://bibliotecavirtual.dgb.umich.mx:8083/xmlui/handle/DGB_UMICH/18561